Pendampingan Ibu Hamil Dalam Upaya Pencegahan Anemia Melalui Metoda Small Group Discussion dan Demonstrasi Pembuatan Kudapan di Desa Karangagung Kecamatan Palang Kabupaten Tuban - Teresia Retna; Wahyuningsin TN; Roudlotul Jannah (Health Community Engagement, 2021)
During pregnancy, the need for nutrients increases, this is necessary to meet the needs of fetal growth and development, and maintenance of maternal health, nutritional deficiencies can lead to anemia. Data from the Tuban Health Office in 2017 of 17,655 pregnant women who suffer from anemia 4,638 (26,2701 %.), in 2018 out of 16,498 pregnant women, 3,331 (20,1903%), while data from Puskesmas Palang the total number of pregnant women in 2019 was 765 people, with 213 pregnant women (28%) experiencing restriction including anemia, while the year 2020 received 317 mothers, 37 mothers with anemia (11.7%), 21 pregnant women (6.6%). The purpose of this PKM-M activity is to provide information, to raise awareness for pregnant women about the importance of fulfilling nutrition for mothers and the fetus during pregnancy to prevent anemia so that they can change the behavior of pregnant women from those who do not understand to be more preventive during pregnancy.The activity was carried out for 2 days using the Small Group Discussion method, an evaluation activity using video calls, which was divided into 5 groups, 1 (one) student coordinating 10 pregnant women, this activity was carried out for 1 week after the meeting. The results of increased knowledge in pregnant women were obtained. with an average of 80,906 before mentoring after mentoring 81.3, discipline and skills in making snacks, there was an increase from before mentoring almost half (44%) who rarely made snacks, to most (56%) pregnant women were motivated and regularly made various forms of snacks, although a small proportion of pregnant women (22%) were still found, who were rarely and never wanted to make snacks.Assistance or interaction through the Small Group Discussion method as a substitute for visits by health workers can make it easier to detect the discovery of new cases of anemia in pregnant women, and the skills of pregnant women are needed, starting from selecting ingredients, food that meets nutritional requirements, processing and serving it as an effort to prevent anemia during pregnancy.